Element-specific and site-specific ion desorption from adsorbed molecules by deep core-level photoexcitation at the K-edges - Baba, Yuji (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
This article reviews our recent works on the ion desorption from adsorbed and condensed molecules at low temperature following the core-level photoexcitations using synchrotron soft x-rays. The systems investigated here are adsorbed molecules with relatively heavy molecular weight containing third-row elements such as Si, P, S, and Cl. Compared with molecules composed of second-row elements, the highly element-specific and site-specific fragment-ion desorptions were observed when we tune the photon energy at the dipole-allowed 1s→s*(3p*) resonance. On the basis of the resonance Auger decay spectra around the 1s ionization thresholds, the observed highly specific ion desorption is interpreted by the localization of the excited electrons (here we call as "spectator electrons") in the antibonding s* orbital. In order to separate the direct photo-induced process from the indirect processes triggered by the secondary electrons, the photon-stimulated ion desorption was also investigated in well-controlled mono- and multilayered molecules. The results confirmed that the resonant photoexcitation not in the substrate but in the thin films of adsorbates plays a significant role in the realization of the highly specific ion desorption.